Does Dividend Policy Moderate the Influence of Financial Performance on Firm Value ? - Kusumawati, Rita; Hadiyanto , Achmad Faisal (Universitas Muhammadiyah Sorong, 2024)
This study tries to demonstrate the elements impacting firm value for manufacturing companies listed on the Indonesia Stock Exchange. Leverage, profitability, and firm size are the variables that were examined in this study. Manufacturing firms registered on the Indonesia Stock Exchange (IDX) for the years 2017–2021 make up the study’s population. Purposive sampling was used to gather the data, and 246 samples were gathered as a result. Multivariate regression analysis (MRA) or interaction tests are used in the study methodology. According to the findings of the hypothesis test, leverage, profitability, and company size all have a positive impact on firm value. The dividend policy can then be used to control the connection between leverage and profitability for firm value.